(untitled) - Tanka, Judith (New York, 1997)
Interactions One: A Listening/Speaking Skills Book, 3/e, is designed to help students develop effective listening strategies that will lead to language acquisition. Students apply new skills to a variety of recorded information including both life skills and academically oriented topics. Ideal for beginning to high-beginning ESOL students.
Keywords: English language,English language,Listening; Spoken english,Problems, exercises, etc,Textbooks for foreign speakers,Problems, exercises, etc